Basic and Grade Stress for Some Timber in Sarawak - Gaddafi, Ismaili; Badorul Hisham, Abu Bakar; Khairul Khuzaimah, Abdul Rahim (UNIMAS Publisher, 2022)
Strength properties’ tests are conducted in the small clear sample. This paper aim to acquire the basic and grade stresses of some fast growing species thus identifies its strength group. Thus, the information of wood properties from different species and condition are acquired from strength property's test. The required information namely, bending parallel to the grain, compression stress parallel to grain, shear parallel to grain and modulus of elasticity. The condition of the trees which is referred to green and air-dry condition. Three different species which are referred to exotic species of Acacia mangium and indigenous species of Aras. The results from the study indicated that, Acacia mangium classified under the strength group SG5, whilst Aras was classified under the strength group SG7. The timber is of medium density Light Harwood ranging from 0.37-0.52g/cm3 air-dry condition.